Factors associated with excess body weight in university students in times of COVID-19: Factores asociados al exceso de peso corporal en estudiantes universitarios en tiempos de COVID-19 - Cruz López, Cinthya Santa (2023)
Introduction: Excess body weight affects the quality of life of millions of young people around the world. Objective: To determine the factors associated with the prevalence of overweight and obesity in university students during COVID-19, from October to December 2020. Methods: Analytical, cross-sectional research with non-experimental design. There was a population of 325 students of the professional career of medical technology and a sample of 169 students of both sexes. Body mass index and waist circumference diameter were used to calculate overweight and obesity. The associated factors were determined by means of a survey validated by expert judgment. Results: 49.1% of the students were overweight or obese, with females being the most affected. Of overweight or obese students, 59.0% were at high risk of abdominal obesity. According to eating habits, 97.6% of young people ate three or more meals per day, 81.9% consumed foods rich in carbohydrates and 54.2% consumed junk food 1 -2 times per week. In relation to sedentary lifestyle, 71.0% of students remained seated between 5 and 8 hours a day, 67.4% slept less than 7 hours a day and 57.8% did not perform any physical activity. Conclusions: The intake of food with high carbohydrate content, junk food, hours spent sleeping and sitting daily are the factors associated with the high prevalence of overweight and obesity among students during the COVID-19 period.